2022
DOI: 10.1097/iae.0000000000003578
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Findings in Choroidal Melanoma-Associated Subretinal Fluid

Abstract: Purpose: To report optical coherence tomography findings of choroidal melanoma with subretinal fluid (SRF).Methods: Single-center, retrospective review of spectral-domain optical coherence tomography in treatment-naive choroidal melanoma with associated SRF presenting between July 2009 and August 2021.Results: Of 236 included patients, choroidal melanoma was small (n = 98, 41.5%), medium (n = 99, 41.9%), or large (n = 39, 16.5%). The most common optical coherence tomography feature was ellipsoid zone loss/disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…1 C). In the recent report but Guner et al [ 23 ] 58% of the eyes with BALAD were associated with heterogenous hyperreflective material. The size and number of BALAD varied among our cases, some were subtle and small (Figs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1 C). In the recent report but Guner et al [ 23 ] 58% of the eyes with BALAD were associated with heterogenous hyperreflective material. The size and number of BALAD varied among our cases, some were subtle and small (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we provide preliminary incidence data on BALAD occurrence with the two most common types of choroidal malignancy and demonstrate an incidence of 54.5% and 14.3% with choroidal metastasis and melanoma, respectively. Recently, Guner et al [ 23 ] reported on the SRF characteristics of a large sample of choroidal melanomas (236 patients). They found the incidence of BALAD to be 28.4%, and that it was more common in medium-sized tumors with larger SRF, which is consistent with our described case of medium-sized malignant melanoma and BALAD.…”
Section: Discussionmentioning
confidence: 99%
“… 14 TFSOM-DIM incorporates multimodal imaging techniques in the identification of risk factors, including subretinal fluid on OCT, orange pigment on autofluorescence, and a basal diameter of at least 0.5 mm on fundus photography. 14 These additional imaging techniques provided a more nuanced approach to identifying UM, 36 which have been evaluated in subsequent studies. Geiger et al used the TFSOM-DIM criteria to grade multimodal imaging by retrospective chart review, revealing significant differences in the range of risk scores between UM and choroidal nevi.…”
Section: Discussionmentioning
confidence: 99%